COVID as a catalyst: shifting experiences of disability and (mis)fitting in the college classroom. Issue 3 (3rd July 2022) - Parsloe, Sarah M.; Smith, Elizabeth M.
ABSTRACT: COVID-19 disrupted traditional face-to-face classroom environments, creating new opportunities for exclusion/inclusion and (in)accessibility. The purpose of this study was to understand students with disabilities' experiences of (mis)fitting (Garland-Thomson, R. (2014). The story of my work: How I became disabled. Disability Studies Quarterly, 34 (2), 1–18. https://dsq-sds.org/article/view/4254/3594 https://doi.org/10.18061/dsq.v34i2.4254 ) in the classroom both before and during the COVID-19 pandemic. Interviews with 16 students revealed how the transition to online learning produced differences in students' embodied experiences of disability and sense of agency in the classroom. Applying cultural contracts theory (Jackson, R. L. (2002). Cultural contracts theory: Toward an understanding of identity negotiation. Communication Quarterly, 50 (3-4), 359–367. https://doi.org/10.1080/01463370209385672 ) and the lens of critical communication pedagogy (Fassett, D. L., & Morella, D. L. (2008). Remaking (the) discipline: Marking the performative accomplishment of (dis)ability. Text and Performance Quarterly, 28 (1-2), 139–156. https://doi.org/10.1080/10462930701754390 ), we explore how the uncertainty of pandemic life inspired some professors to loosen rigid expectations of what "ideal" student participation looks like, exchanging ready-made contracts for quasicomplete and cocreated contracts. In addition, we consider how an uncritical return to "normal" might reassert ableist policies and practices.